Programmable and Sequence‐Selective Supramolecular Assembly of Two Different Chromophores along DNA Templates. Issue 61 (9th October 2018) - Hofsäß, Robert; Sinn, Stephan; Biedermann, Frank; Wagenknecht, Hans‐Achim
Abstract: The templated self‐assembly of two different chromophores attached to the same binding motif gives oligomers of statistical mixtures without any control on the resulting chromophore sequence. The first self‐assembled bichromophore system is reported, in which the resulting chromophore sequence is simply governed by the DNA template. A new ethynylpyrene‐diaminopurine 2′‐deoxynucleoside was combined with the ethynyl nile red‐modified 2′‐deoxyuridine to achieve this completely programmable sequence selective self‐assembly. The helical ordering of the two different chromophores by DNA templates with different mixtures of A‐T sequences yields precise control over the optical properties of the formed assemblies, which was proven by methods of optical spectroscopy. Abstract : The first self‐assembled bichromophore system is reported, in which the resulting chromophore sequence is simply governed by the DNA template. A new ethynylpyrene‐diaminopurine 2′‐deoxynucleoside was combined with the ethynyl nile red‐modified 2′‐deoxyuridine to achieve this completely programmable sequence selective self‐assembly.